Genome-wide identification and tissue-specific expression analysis of UDP-glycosyltransferases genes confirm their abundance in cicer arietinum (chickpea) genome - Sharma, Ranu; Rawat, Vimal; Suresh, C. G. (Plos One, 2014)
UDP-glycosyltransferases (EC 2.4.1.x; UGTs) are enzymes coded by an important gene family of higher plants. They are involved in the modification of secondary metabolites, phytohormones, and xenobiotics by transfer of sugar moieties from an activated nucleotide molecule to a wide range of acceptors. This modification regulates various functions like detoxification of xenobiotics, hormone homeostasis, and biosynthesis of secondary metabolites. Here, we describe the identification of 96 UGT genes in Cicer arietinum (CaUGT) and report their tissue-specific differential expression based on publically available RNA-seq and expressed sequence tag data. This analysis has established medium to high expression of 84 CaUGTs and low expression of 12 CaUGTs. We identified several closely related orthologs of CaUGTs in other genomes and compared their exon-intron arrangement. An attempt was made to assign functional specificity to chickpea UGTs by comparing substrate binding sites with experimentally determined specificity. These findings will assist in precise selection of candidate genes for various applications and understanding functional genomics of chickpea.

Genome-wide identification and structure-function studies of proteases and protease inhibitors in cicer arietinum (chickpea) - Sharma, Ranu; Suresh, C. G. (Computers in Biology and Medicine, 2015)
Background: Proteases are a family of enzymes present in almost all living organisms. In plants they are involved in many biological processes requiring stress response in situations such as water deficiency, pathogen attack, maintaining protein content of the cell, programmed cell death, senescence, reproduction and many more. Similarly, protease inhibitors (PIs) are involved in various important functions like suppression of invasion by pathogenic nematodes, inhibition of spores-germination and mycelium growth of Alternaria alternata and response to wounding and fungal attack. As much as we know, no genome-wide study of proteases together with proteinaceous PIs is reported in any of the sequenced genomes till now. Methods: Phylogenetic studies and domain analysis of proteases were carried out to understand the molecular evolution as well as gene and protein features. Structural analysis was carried out to explore the binding mode and affinity of PIs for cognate proteases and prolyl oligopeptidase protease with inhibitor ligand. Results: In the study reported here, a significant number of proteases and PIs were identified in chickpea genome. The gene expression profiles of proteases and Pis in five different plant tissues revealed a differential expression pattern in more than one plant tissue. Molecular dynamics studies revealed the formation of stable complex owing to increased number of protein-ligand and inter and intramolecular protein-protein hydrogen bonds. Discussion: The genome-wide identification, characterization, evolutionary understanding, gene expression, and structural analysis of proteases and Pis provide a framework for future analysis when defining their roles in stress response and developing a more stress tolerant variety of chickpea. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Domain; Gene expression; Genome analysis; Homology modelling; Molecular docking; molecular dynamics simulation; Motif; Orthologs; Phylogeny